ALGUNS PRINCÍPIOS DO SISTEMA ALFABÉTICO DO PB PARA O ENSINO DA LEITURA A FALANTES DO ESPANHOL - Scliar-Cabral, Leonor (Intercâmbio, 2010)
A tool for teaching second languages to non native adult is developing metalinguistic and metacognitive strategies, which may facilitate overcoming those difficulties they have due to their conditioning of perceptual features and vocal gestures diverging from the language to be learnt. The alphabetic system of the Brazilian Portuguese language is one of those tools, by virtue of its extreme transparency on decoding.